Beyond code: handling variability in art artifacts in mobile game product lines - Alves, Vander (2006)
This position paper addresses on going work in exploring variability mechanisms for relevant artifacts in the domain of Mobile Game Software Product Lines. In particular, we show such mechanisms for images and sound and reason on the choice of such mechanism based on factors such as binding-time, performance, and reusability. Future work consists of refining a reasoning framework to encompass additional factors for the selection of such mechanism and exploring more closely the influence of such artifacts not only in code but also in tests.